Pengaruh pendekatan contextual teaching and learning (CTL) terhadap kemampuan penalaran matematis siswa kelas VIII SMP Negeri 5 Ujungbatu - Zulwansyah; Ario, Marfi; Isharyadi, Ratri (Jurnal Pendidik Indonesia, 2020)
This study aims to determine whether the Contextual Teaching and Learning (CTL) approach influences the mathematical reasoning ability of 8th-grade students at SMP Negeri 5 Ujungbatu. The research design used is a Quasi-Experiment with a Two Group Posttest Only design. The population in this study consists of the 8th-grade classes at SMP Negeri 5 Ujungbatu. Sampling was done using Random Sampling, selecting two classes as sample groups. Class VIII.1 was the experimental group, and Class VIII.3 was the control group. The instrument in this study is a test of mathematical reasoning ability given to the sample classes. The normality test, conducted using the Lilliefors test, showed that both Class VIII.1 and VIII.3 had non-normal distributions. Based on the hypothesis test using the Mann-Whitney test, the calculated value (t count) was 228, and the tabulated value (t table) was 87. This indicates that t count ≥ t tabel, leading to the rejection of the null hypothesis (H0). Therefore, it can be concluded that the Contextual Teaching and Learning (CTL) approach influences the mathematical reasoning ability of 8th-grade students at SMP Negeri 5 Ujungbatu.